Convivendo com a loucura: as representações sociais dos líderes comunitários - Sanford, Fátima de Maria Sales (2000)
The everday i ve lived as a psychiatric nurse in a community woke up our interest in indentifying lhe social representations of the community leaders about realizing and dealing with crazy beings. This research have been developed in a qualitative approach, supported by the Social Representatíon Theory, in the perspective of the Social Psychology, according to M0SC0V1CI. It was made at the Dendê Community, Fortaleza - Ceará - Brazil, from july to august, 1999. The researchers were twelve community leaders. The speeches have been colected through "depth” or "focus", starting from such questions: Wath is being crazy? How do you identify the crazy person? What is your reaction to those people? What cause insanity to community leaders? How couíd yoü and the community heir those people? The data have been analized according to Bardin's content analysis, following the thematic analysis procedures. In the community leaders, presentations, the construction of insanity is related to the individual contents linked to the subjective living of the fellows and the cultural contents of their social environment. The social representations of madness mostly occur around figurativo sketches, like: not having a perfect mind, losing the meaning of life, disturbing the environment, and to not believe in God. The causes of insanity were mentioned like heredity, social and economic conditions, psicosocial, familiar conditions, drugs use and spirituality. Also appeared, as social presentations, agressive behavlor, infantile, different, and dificulties in communication. The leaders showed positive affectivity, presented through acceptance, distrust and fear to the mad ones. We realized that the leaders could welcome, envolve the community to help these people, find techical help, create conditions to watch íhem in the community, sharing responsabilities and sending them to hospitais. It was possible to identifyíng the social presentations about madness and the way to act in front of it, faciliíating the developmení of new actions and more adapted to the reality lived in the researched context.